Investigation of flame structure and burning intensity of partially premixed methane enrichment of syngas using OH-PLIF and kinetic simulation. Issue 3 (4th May 2018) - Pu, Ge; Huang, Beibei; Zhang, Xun; Du, Jiantai; Zhu, Tuanhui; Chen, Bei
Abstract : Various experiments were conducted to study the combustion characteristics of partially premixed methane enrichment of syngas by using the OH-PLIF technique. Experiments were conducted on a co-flow burner, and the methane concentration ( XCH4 = CH4 /(H2 +CO+CH4 )) was varied from 0 to 20%, the overall equivalence ratio was varied from 0.4 to 1.2 and the inner equivalence ratio was varied from 1.5 to 3.5. Kinetic simulation was conducted by using OPPDIF module of CHEMKIN-Pro software. Results show that an increase in XCH4 and ϕ overall weakens the OH signal intensity. Adding methane into the fuel greatly increases the height of the inner flame front, and the increase of methane concentration has a negative effect on flame propagation speed. Meanwhile, simulation results remain consistent with the experiments. The main OH radical production reaction changes from R46: H+HO2 = 2OH to R38: H+O2 = O+OH when methane concentration contained in the fuel mixture increases. Sensitivity analysis also indicates that reaction which plays a dominant effect on temperature changes with the increase of methane concentration.